The breaking news - Reul, Sarah Lynne (Roaring Brook Press, 2018)
When devastating news rattles a young girl's community, her normally attentive parents and neighbors are suddenly exhausted and distracted. At school, her teacher tells the class to look for the helpers-the good people working to make things better in big and small ways. She wants more than anything to help in a BIG way, but maybe she can start with one small act of kindness instead ... and then another, and another. Small things can compound, after all, to make a world of difference. Both timely and timeless, this charmingly illustrated debut picture book from Sarah Lynne Reul touches on themes of community, resilience, and optimism with an authenticity that will resonate with readers young and old.